Everyday Digital Schooling - implementing tablets in Norwegian primary school - Rune Johan Krumsvik; Erling Berrum; Lise Øen Jones (Universitetsforlaget, 2018)
Abstract Implementation of tablets in Norwegian schools has become quite common, but we still have too little research knowledge about the learning outcome from these implementation measures. To achieve more knowledge about the topic, this trailing research examines the first cohort of Bærum municipality's implementation of tablets in primary school. The outcome measures in the study are external for the intervention, and are recorded data from National Tests (National reading, arithmetic and English Tests, Classes 5, 8 and 9, National Mapping Tests for reading and arithmetic, Classes 1-3, and the 2014-2016 National Pupil Survey). The whole study (N=15,708) relies on an explanatory, sequentially mixed-methods design (Fetters, Curry and Creswell (2013), and in this study we examine the quantitative effects of this implementation. The results stemming from the general focus areas, that is, spelling, reading, comprehension and arithmetic in the National Mapping Tests for reading for Classes 1-3, we find that there is no significant impact on pupil learning with respect to Classes 1 and 2 at the Pilot 1 schools in 2015 and 2016, compared with the results obtained for the other Bærum schools. The same applies to Class 3, with the exception of arithmetic, where we see negative results as a consequence of being a pilot school and having used tablets. This differs to what we see in the results of the National Tests for Class 5 in 2015 and 2016, where we note significant positive outcomes with respect to arithmetic and English among boys at the pilot schools, compared with Class 5 boys at the other Bærum schools. The findings is only based on the first nine months from the implementation of tablets and therefore a second cohort of research is recommended in order to validate and elaborate on these preliminary findings.